2003
DOI: 10.1097/00004836-200310000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Retards the Progression of Alcohol-Induced Hepatic Fibrosis in Baboons

Abstract: Silymarin retards the development of alcohol-induced hepatic fibrosis in baboons, consistent with several positive clinical trials. The negative outcome observed in other trials possibly reflects poor compliance resulting in irregular or low silymarin intake. Thus, in view of the innocuity of silymarin, it might be advisable in future clinical studies to insure the controlled administration of sufficient amounts of silymarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 9 publications
2
81
0
4
Order By: Relevance
“…Such compounds show protective effects against agent-induced hepatic injuries (Berger & Kowdley, 2003;Lieber et al, 2003;Hedayat et al, 2004). Other studies state that silymarin exhibited antioxidant action (Soto et al, 2003;Chlopcikova et al, 2004;Lieber, 2004) and showed promising antineoplastic and immunomodulatory effects (Amirghofran et al, 2000;Hannay & Yu, 2003;Schümann et al, 2003;Yoo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds show protective effects against agent-induced hepatic injuries (Berger & Kowdley, 2003;Lieber et al, 2003;Hedayat et al, 2004). Other studies state that silymarin exhibited antioxidant action (Soto et al, 2003;Chlopcikova et al, 2004;Lieber, 2004) and showed promising antineoplastic and immunomodulatory effects (Amirghofran et al, 2000;Hannay & Yu, 2003;Schümann et al, 2003;Yoo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…S. marianum or milk thistle (MT) is the most well-researched plant in the treatment of liver disease and has been used to treat ALD and acute and chronic viral hepatitis. In baboons, the active principle called silymarin, administered for 3 years, retarded the development of alcohol-induced hepatic fibrosis [195] . The major mechanism of its hepatoprotective activity is the inhibition of hepatic NF-κB activation.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Silymarin suppressed the expression of pro-fibrogenic procollagen-α1(I) and TIMP-1 most likely via down-regulation of TGF-β1 mRNA in the rats with biliary fibrosis (Jia et al 2001). Silymarin, administered during three years, retarded the development of alcohol-induced hepatic fibrosis in baboons (Lieber et al, 2003).…”
Section: Antifibrotic Activitymentioning
confidence: 99%